1966
DOI: 10.1111/j.1365-2141.1966.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenaline and Experimental Thrombosis*

Abstract: The acceleration of blood coagulation in vivo by adrenaline was first demonstrated by Vosburgh and Richards in 1903. They showed in man that adrenaline in doses of 7 μg. per kg. body weight shortened the coagulation time by about 50 per cent. Subsequent studies led to conflicting conclusions until the experiments of Cannon and Gray in 1914, who showed that small doses of adrenaline promoted coagulation, but that larger doses inhibited it. This was confirmed by later investigators (Waldron, 1951; Forwell and In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The possible pathophysiological link between blood loss and haemostatic activation is unknown, but studies in animals and humans seem to suggest that neurohumoral, in particular adrenergic, mechanisms could be involved [34][35][36][37][38][39]. The neurohumoral response to haemorrhage is complex, however, and may depend on factors such as the species investigated, the amount of blood lost and the use of anaesthesia [40].…”
Section: Rahr/roman/ingerslev/jørgensenmentioning
confidence: 99%
“…The possible pathophysiological link between blood loss and haemostatic activation is unknown, but studies in animals and humans seem to suggest that neurohumoral, in particular adrenergic, mechanisms could be involved [34][35][36][37][38][39]. The neurohumoral response to haemorrhage is complex, however, and may depend on factors such as the species investigated, the amount of blood lost and the use of anaesthesia [40].…”
Section: Rahr/roman/ingerslev/jørgensenmentioning
confidence: 99%
“…As catecholamines or drugs acting on catecholamine metabolism can influence brain functions and behaviour (Hornykiewicz, 1966 ;Brodie, Spector & Shore, 1959;Dewhurst, 1968), vasoregulation (Furchgott, 1955), thrombus formation (Rowsell, Carbon disuilphide on brain catecholamines Hegardt, Downie, Mustard & Murphy, 1966), lipid metabolism (Wirsen, 1965), the development of cardiovascular lesions (Mehes, Papp & Rajkovits, 1967;David, Hecht & Uerlings, 1968 ;Nityanand, 1967 ;Whittington-Coleman, Carrier & Clower, 1968), the effect of CS2 on catecholamine metabolism might be a common denominator for the development of carbon disulphide intoxication. This hypothesis that CS2 acts on the metabolism of catecholamines gained support by reports that disulfiram (Goldstein, Anagnoste, Lauber & McKereghan, 1964;Musacchio, Kopin & Snyder, 1964) and diethyldithiocarbamate (DDC) (Carlsson, Lindquist, Fuxe & Hokfelt, 1966;Edington, 1968) inhibit dopamine-p-hydroxylase, and disulfiram is metabolized through DDC to CS2 (Johnston & Prickett, 1952;Fischer & Brantner, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell and Sharp (1964) found that both amines accelerated platelet clumping. Rowsell et al (1966) and noradrenaline on platelet aggregation in vitro. He also suggested (O'Brien, 1964a) that these catecholamine effects might be due to the stimulation of an adenosine triphosphatase.…”
Section: Diurnal Variationsmentioning
confidence: 96%